Exploring the Principles for Adults' Mathematical Literacy Education Using an Interdisciplinary Educational Approach - Ryoonjin Song (Korea Society of Educational Studies in Mathematics, 2022)
Mathematical literacy constitutes a basic arithmetic skill in traditional society; however, its concept has evolved to applying mathematical knowledge and ideas to solve diverse and complex real-world problems and to improve people's lives and society at large. In this context, a new paradigm is necessary for adult mathematics learners to cultivate the mathematical literacy required in a knowledge-convergence society. Based on an extensive literature review related to adult mathematics education and interdisciplinary education, the researcher proposes the goals of adult mathematics education and the principles to develop a curriculum using an interdisciplinary educational approach. The approach used in this study may form the basis for implementing mathematical literacy education in adults.